2021
DOI: 10.1177/01626434211054441
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Physics to Students With Intellectual Disabilities Using Digital Learning Objects

Abstract: Digital Learning Objects (DLOs) as pedagogical complete structures of learning content contribute to science education. DLOs especially in the form of interactive simulations seem to be promising tools in physics teaching and learning for students with intellectual disabilities (ID). This study used an AB single subject design to evaluate the effects of four DLOs on students’ learning of transverse waves and simple pendulum motion in a special education high school setting. A functional relationship was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…In recent years, technology has played an increasingly important role in assisting teachers with the instruction of science subjects, especially for students with disabilities (McKissick et al, 2018;Turan & Atila, 2021;Wright et al, 2021). Numerous studies have demonstrated the various applications of technology in this context, including serving as a direct instructional instrument (Gavronskaya et al, 2021) and facilitating the creation of interactive educational materials (Mallidis-Malessas et al, 2022;Ok et al, 2018). It has been demonstrated that these engaging and dynamic resources effectively captivate the attention of the intended learner population while simultaneously increasing their motivation (Ok et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, technology has played an increasingly important role in assisting teachers with the instruction of science subjects, especially for students with disabilities (McKissick et al, 2018;Turan & Atila, 2021;Wright et al, 2021). Numerous studies have demonstrated the various applications of technology in this context, including serving as a direct instructional instrument (Gavronskaya et al, 2021) and facilitating the creation of interactive educational materials (Mallidis-Malessas et al, 2022;Ok et al, 2018). It has been demonstrated that these engaging and dynamic resources effectively captivate the attention of the intended learner population while simultaneously increasing their motivation (Ok et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An additional issue warranting attention is the implementation and assessment of educational practices, particularly as they pertain to students with disabilities. It is essential to consider the unique circumstances of these students when applying various methodologies (King-Sears & Johnson, 2020;Mallidis-Malessas et al, 2022;Villanueva & Di Stefano, 2017). Apanasionok et al (2020) highlight that students with developmental disabilities encounter difficulties accessing mainstream science programs, which consequently exacerbates the science attainment gap between students with and without disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Τα ΨΜΑ που αφορούν τη νοητική αναπηρία έχουν σχεδιαστεί με προσαρμογές και διευκολύνσεις για τους μαθητές, ακολουθώντας τον Καθολικό Σχεδιασμό για τη Διδασκαλία και τη Μάθηση, καθώς και τις προαναφερόμενες διδακτικές τεχνικές της ανάλυσης έργου, της χρονικής καθυστέρησης και των προτροπών ενσωματωμένες στην διδακτική προσέγγιση της δομημένης διερεύνησης (Mallidis-Malessas et al, 2021).…”
Section: τα ψηφιακα μαθησιακά αντικείμεναunclassified
“…There are several advantages to the use of ICT in the educational setting. These advantages include making learning more interesting and interactive for students (Adam & Ray, 2020;Braslauskienė et al, 2017); provide more effective learning opportunities to students with special needs (Istenic Starcic & Bagon, 2014;Mallidis-Malessas et al, 2022); enabling more efficient completion of homework and group work (Agasisti et al, 2020;Melander Bowden & Svahn, 2020); being a versatile tool for teachers with its ability to be used in different courses (Baez Zarabanda, 2019); helping teachers identify and address the specific needs of their students and improve teachers' professional competencies by using various ICT tools in the classroom (Braslauskienė et al, 2017;Ocampo-Botello et al, 2019). Overall, the use of ICT in education can lead to more effective and efficient teaching and learning processes and better prepare students for the digital world they will encounter in their future careers (Braslauskienė et al, 2017).…”
Section: Introductionmentioning
confidence: 99%